The Contextual Effect of Posyandu on the Decision to Use Long Term Contraceptive in Tulungagung, East Java - Frafitasari, Dika Yanuar; Budihastuti, Uki Retno; Murti, Bhisma (Journal of Maternal and Child Health, 2020)
Background: Family planning will help reduce population growth, fertility, improvement quality of life, women’s health status, unwanted pregnancy, and abortion. The selection of the use of con